California Penal Code Sec. 270.1: A Constitutionally Impermissible Attempt to Combat Truancy - Cordova, Alison (2011)
In the 2008-2009 academic school year, over a quarter of the California public school student population was truant. There is a well established correlation between truancy and dropping out of high school. And high school dropouts make up over three quarters of the prison population of the State of California. Responding to this alarming domino effect, the California Legislature enacted Penal Code section 270.1 in September, 2010. This statute imposes criminal liability on parents of chronically truant students for not encouraging or supervising their child's school attendance. While the aim of this law is clearly to attack criminality before it takes root in young adults, nevertheless this law may infringe on parents' constitutionally protected fundamental rights of autonomy in childrearing. In parent-child relationship cases, the United States Supreme Court reveres the role of parents, but also recognizes the State's right to intervene on behalf of a child's welfare. The Court weighs the reasonability of the parental decision against the reasonability of the state's infringement to determine the constitutionality of a law that aims to affect this highly regarded relationship. To be reasonable, state infringement must be appropriately designed to address the state's interest. Empirical research tends to indicate that laws that impose liability on parents for the conduct of their children-like Penal Code section 270.1- will most likely not increase school attendance among truant children. The conclusions of far-reaching studies necessarily conflict with the proposition that Penal Code section 270.1 is appropriately designed to address the State's interest. Therefore, Penal Code section 270.1 rests on unstable constitutional grounds. Its foundation is further weakened because other methods of school reform exist that would more likely improve school attendance without infringing on parental autonomy